Design of a Web-Based Inventory Management System for the Nutrition Installation at Harapan Sehat Hospital, Jatibarang - Yuniarti, Deni; Jaka Subrata (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The rapid development of information technology has had a significant impact on various sectors, particularly in business and economics. In the context of data management within companies, inventory systems play a crucial role in minimizing the potential manipulation of company assets. The inventory management system, which was originally handled manually, has now evolved into a website-based system. The main goal of this development is to reduce human error and increase efficiency in recording the flow of goods in and out. This system, designed specifically for the Nutrition Installation at Harapan Sehat Hospital in Jatibarang, aims to assist staff in efficiently recording and managing inventory while generating accurate reports based on the required data. The website is built using MySQL as the database for storing inventory information, with CSS and HTML for the interface, and PHP as the programming language to implement the system's functionality. This research employs a qualitative analysis approach, with data collection techniques including observations and interviews for primary data, as well as notes, books, and documents related to inventory as secondary data. It is expected that this inventory management system will effectively support inventory management needs at Harapan Sehat Hospital in Jatibarang, facilitating more efficient and accurate inventory control.